Kesejahteraan dan Ekologi Anak Angkat Warga Negara Indonesia dalam Pengangkatan Anak AntarNegara (Intercountry Adoption) Menghadapi Negara Baru - Susanto, Monica Sundawati; Imelda, Johanna Debora (UI Scholars Hub, 2021)
Adoption is currently one of the efforts chosen by several couples to have children. Adoption of children currently being processed in Indonesia is not only for prospective adoptive parents who are Indonesian citizens, but can also be processed for foreign citizens who wish to adopt Indonesian citizens (intercountry adoption) which has been regulated in the Government through Government Regulation Number 54 of 2007 concerning the Implementation of Child Adoption. In these regulations, children who can be adopted are neglected or neglected children. Therefore, adoption is carried out with the aim of protecting and improving the welfare of the child. The welfare of the child also needs to be considered from the aspect of changes in the ecology of the child, who previously lived in the Indonesian state, then there was a change in the environment of a new country abroad. This article aims to identify the welfare and ecology of international adopted children of Indonesian citizens (intercountry adoption) who previously lived in Indonesia and after being processed for adoption by foreigners who were taken abroad by foreign adoptive parents. This research uses qualitative methods with descriptive types. Collecting data in this study using documentation study, observation, and interviews. There are 10 informants based on purposive sampling. The results of this study found that the adopted children of Indonesian citizens who were taken to the country of their adopted parents of foreigners were in a prosperous condition with their subjective and objective welfare needs being met. The recommendations in this study are conveyed to the Ministry of Social Affairs as a government agency that has the authority for the process of adoption between countries to increase efforts to monitor and evaluate the development of post-adoption children. The Sayap Ibu Foundation as a childcare institution that has the authority to adopt a child needs to have more information about children adopted until the child is 18 years old, and also there is a need for a database of locations and family contacts of post-adopted children, both by the Ministry of Social Affairs, The Sayap Ibu Foundation and the Ministry of Home Affairs especially Population Affairs and Civil Registry